Magnetic Susceptibility of Volcanic Rocks from Pahae Julu Region, North Sumatera Province - Nurmala Dewi Siregar; Hamdi Rifai; Syafriani Syafriani; Ahmad Fauzi; Fatni Mufit (Diponegoro University Semarang Indonesia, 2022)
Pahae Julu is a sub-district located in North Tapanuli Regency, North Sumatra. This area is often found with volcanic material from the eruption of Mount Toba (Youngest Toba Tuff). The Youngest Toba Tuff eruption occurred 74,000 years ago with a volume of 2,800 km3. When there is an eruption, the lava on the earth's surface undergoes a relatively fast freezing process to form volcanic igneous rock. These rocks contain various minerals, one of which is magnetic minerals that can be used as a track record of volcanic processes from Mount Toba. However, no document records the magnetic susceptibility value of the Youngest Toba Tuff volcanic rock in the Pahae Julu area. This research aimsbfor knowing the abundance of magnetic minerals by the low-field magnetic susceptibility. To achieve this goal, the rock magnetism method is used. This way is very effective, cheap, sensitive, and non-destructive. Magnetic susceptibility measurements are done using the Bartington Magnetic Susceptibility Meter MS2B sensor. Rock samples analyzed are pumice which is the result of the Youngest Toba Tuff eruption. The results showed that the magnetic susceptibility value obtained for the sample was between 85.0 x 10-8m3/kg – 183.1 x 10-8m3/kg with an average of 119.78 x 10-8m3/kg. Based on this value, it is assumed that the magnetic mineral properties are Antiferromagnetic. The average value of χ fd% obtained is 0.95%, indicating that the Youngest Toba Tuff volcanic rock in the Pahae Julu area has almost no Superparamagnetic grains.